Genetic mapping shows intraspecific variation and transgressive segregation for caterpillar‐induced aphid resistance in maize. Issue 22 (6th November 2015) - Tzin, Vered; Lindsay, Penelope L.; Christensen, Shawn A.; Meihls, Lisa N.; Blue, Levi B.; Jander, Georg
Abstract: Plants in nature have inducible defences that sometimes lead to targeted resistance against particular herbivores, but susceptibility to others. The metabolic diversity and genetic resources available for maize ( Zea mays ) make this a suitable system for a mechanistic study of within‐species variation in such plant‐mediated interactions between herbivores. Beet armyworms ( Spodoptera exigua ) and corn leaf aphids ( Rhopalosiphum maidis ) are two naturally occurring maize herbivores with different feeding habits. Whereas chewing herbivore‐induced methylation of 2, 4‐dihydroxy‐7‐methoxy‐1, 4‐benzoxazin‐3‐one glucoside (DIMBOA‐Glc) to form 2‐hydroxy‐4, 7‐dimethoxy‐1, 4‐benzoxazin‐3‐one glucoside (HDMBOA‐Glc) promotes caterpillar resistance, lower DIMBOA‐Glc levels favour aphid reproduction. Thus, caterpillar‐induced DIMBOA‐Glc methyltransferase activity in maize is predicted to promote aphid growth. To test this hypothesis, the impact of S. exigua feeding on R. maidis progeny production was assessed using seventeen genetically diverse maize inbred lines. Whereas aphid progeny production was increased by prior caterpillar feeding on lines B73, Ki11, Ki3 and Tx303, it decreased on lines Ky21, CML103, Mo18W and W22. Genetic mapping of this trait in a population of B73 × Ky21 recombinant inbred lines identified significant quantitative trait loci on maize chromosomes 1, 7 and 10. There is a transgressive segregation for aphid resistance, with the Ky21 alleles on chromosomes 1 and 7 and the B73 allele on chromosome 10 increasing aphid progeny production. The chromosome 1 QTL coincides with a cluster of three maize genes encoding benzoxazinoid O‐ methyltransferases that convert DIMBOA‐Glc to HDMBOA‐Glc. Gene expression studies and benzoxazinoid measurements indicate that S. exigua ‐induced responses in this pathway differentially affect R. maidis resistance in B73 and Ky21.